Effect of cooling on muscular health prior to running a marathon - Liang, M. T.; Allen, T. W.; McKeigue, M. E.; Kotis, A.; Gierke, L. W. (The Journal of the American Osteopathic Association, 2001)
To examine the effects of a prerace whole-body cold shower on muscle soreness (MS) and on serum creatine kinase (CK) and creatine kinase MB (CK-MB) isoenzyme activities, 16 experienced distance runners were randomly assigned to one of two treatment categories prior to running a marathon: cold shower (n = 8) or without cold shower (n = 8). Venous blood samples were drawn 3 days before the race, 10 minutes before the race, immediately (within 3 minutes) after the race, and at 1, 24, 48, and 96 hours postrace. Nine muscle sites were evaluated for soreness 10 minutes before the race, immediately after the race, and at 24, 48, and 96 hours postrace. The results showed a marked (P < .05) difference between the cold shower group and the group without cold showers for CK-MB/CK ratio, and no difference for CK, CK-MB, and MS. Both CK and CK-MB values peaked at 24 hours postrace. MS occurred most frequently immediately after the race and at 24 hours postrace. The MS was completely resolved in all subjects by 96 hours postrace. The most frequently reported sites of MS were the quadriceps, followed by the gastrocnemius, the soleus, and the tibialis anterior. Severe MS was rated highest at the quadriceps and the soleus, and the least at the gastrocnemius and the tibialis anterior. The data suggest that prerace whole-body cold showers neither prevented the production of serum CK and its MB fraction, nor attenuated MS after a marathon. Peak serum CK and CK-MB activity was not associated with the onset of MS.